Influence of yttrium and niobium oxides modifiers on physicochemical and photocatalytic properties of titanium (IV) oxide - Kyrii, Svitlana; Dontsova, Tetiana; Kosogina, Iryna; Podopryhor, Valeriia; Serhiienko, Alla (Eastern-European Journal of Enterprise Technologies, 2021)
The photocatalytic and physicochemical properties of titanium (IV) oxide modified by yttrium and niobium oxides were studied. It is shown that modification is a powerful way to increase the efficiency of catalysts’ photocatalytic properties and improve the photocatalytic process as a whole. Commercial and laboratory-synthesized titanium (IV) oxides were used as catalysts for modification. Modification of titanium (IV) oxide powders in an amount of 1 wt. % by appropriate modifiers was performed by the hydrothermal method, after which they were characterized by diffraction and X-ray fluorescence methods. The structural characteristics of modified and non-modified titanium (IV) oxide samples by the method of low-temperature nitrogen adsorption-desorption have been studied. A slight increase in the specific surface area was found: from 61 m2/g to 70 m2/g for the commercial sample and from 172 m2/g to 180 m2/g for the synthesized one in this work. Similar dependencies are observed when studying the optical properties by the spectrophotometric method. Determination of surface properties (surface acidity) of modified and non-modified photocatalysts based on TiO2 showed different effects of modifiers on TiO2 acidity: in the modification by yttrium oxide, the acidity decreases, and in the case of niobium oxide – increases. Studies of photocatalytic and sorption activities with respect to dyes of different nature are not the same – the photocatalytic activity after modification increases, the sorption capacity with the cationic dye decreases, anionic – increases. Additional studies on dye destruction are in full accordance with photocatalytic and sorption experiments.